Activated Sludge and other Aerobic Suspended Culture Processes. (1st October 2018) - Li, Chunying; Zhao, Yunfa; Ouyang, Jia; Wei, Dong; Wei, Li; Chang, Chein‐Chi
Abstract : In this paper, removal model of activated sludge, cultivation and application of granular sludge, the population dynamics, removal and influence of toxic pollutants, and design and control of the sewage treatment system are reviewed in 2017. Several studies suggest that the cultivation of granular sludge is mainly affected by aeration rate, hydraulic velocity and culture environment. Toxic pollutants can be partially degraded by microorganisms, which lead to the change of microbial community structure. The co‐digestion of activated sludge and other solid wastes can produce biomass energy, which is a more promising and solid waste treatment method.